Secret Chambers: The Insider Story of Cells and Complex Life - Farid Pazhoohi (Ethnobiology Letters, 2014)
Review of Secret Chambers: The Insider Story of Cells and Complex Life. Martin Brasier. 2012. Oxford University Press, UK. Pp. 320 with 15 black and white illustrations and 8 pages of color plates. £16.99 (hardcover). ISBN 9780199644001.